Social and Cultural Integration: A Discourse Analysis of Islamic Themes in the Basis Magazine, 1998–2000 - Yuliantri, Rhoma Dwi Aria (Indonesian Historical Studies, 2024)
This article examines the discourse on Islam found in articles published in Basis from 1998 to 2000. Basis is a cultural magazine founded in Yogyakarta by members of the Society of Jesus (SJ) in 1951. Since 1998, Basis has regularly featured writings on Islamic themes contributed by both Muslim and non-Muslim intellectuals. This research aims to understand why Basis, with its Catholic missionary vision and spirit, embraced Islamic themes during the 1998–2000 period and to what extent these Islamic and Islamic-themed articles reflect the journal's mission of interreligious dialogue in response to the "cultural freedom" of the Reform Era. A historical methodology using text analysis techniques was employed for this research. Primary sources included articles with Islamic themes published in Basis between 1998 and the early 2000s, as well as interview data. The findings indicate that following the fall of the New Order regime in 1998, Indonesia experienced "cultural freedom," including increased freedom of expression, which significantly influenced the media landscape. Basis' inclusion of articles with Islamic themes was a response to this "cultural freedom" in the contemporary context. The Islamic discourse presented in Basis primarily focused on contextual issues related to religious polarization and conflicts in Indonesia at the dawn of the Reform Era, including discussions on pluralism and the significance of interreligious dialogue within the framework of the nation-state. The Islamic discourse in Basis demonstrated a fluid nature, suggesting coexistence and close interaction among adherents of various value systems and worldviews.